Monthly and diurnal variations of limnological conditions of two ponds (International Journal of Agricultural Research, Innovation and Technology, 2017)
A study on monthly and diurnal changes of limnological conditions of two ponds was conducted in the Bangladesh Agricultural University campus, Mymensingh. The research work was performed by studying the limnological parameters such as transparency, temperature, dissolved oxygen, free carbon dioxide, pH, total alkalinity, nitrate-nitrogen, phosphate-phosphorus and plankton. Diurnal variations of physico-chemical factors were studied fortnightly at 6 hrs intervals at 6 a.m., 12 noon, 6 p.m. and 12 midnight. The amounts of transparency, dissolved oxygen and pH were higher during winter months than in summer months in both the ponds. Transparency, water temperature, total alkalinity, NO3-N and PO4-P were higher during summer months than in winter months in both the ponds. But the amount of free carbon dioxide was higher during winter months than in summer months in pond 1 while in pond 2 the amount of free carbon dioxide was higher during summer months than in winter months. Qualitative and quantitative monthly variations of phytoplankton and zooplankton were observed in both the ponds during the study period. The highest amount of dissolved oxygen, pH and total alkalinity were recorded at 6 p.m. and the lowest amounts of those at 6 a.m. in both the ponds. The highest temperature was recorded at 12 noon and the lowest at 12 midnight. But the highest amount of free carbon dioxide was recorded at 6 a.m. and the lowest at 6 p.m. in both the ponds. All the factors showed appreciable diel variations throughout the study period, which indicate that the ponds are productive.Int. J. Agril. Res. Innov. & Tech. 7 (1): 14-20, June, 2017